Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve the system using elimination. x – y = –5 3x + y = 1
(–1, 4)
(–1, 2)
(2, –2)
(–3, 4)


Sagot :

Answer:

(–1,4)

Step-by-step explanation:

x – y = –5

3x + y = 1

You omit Ys due to their positive and negative signs and you got

4x = –4===> x= –1

and now place –1 inside the upper linear equation and there you have the Y, look

–1 – Y= –5===> –Y= –4===> Y = 4

(–1,4)